Rural Tourism Entrepreneurship Skills and Knowledge as Strategy for Poverty Reduction: A Case of Bagamoyo District, Tanzania - Mungure, Jossam S; Kalwani , Jumanne D (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2025)
Entrepreneurship is a process and art of managing business which needs an entrepreneur to have relevant sets of entrepreneurial skills and knowledge. These sets are considered as an alternative tool to minimize socio economic problems especially problem of high unemployment, environmental pollution, and poverty. The paper established entrepreneurship skills and knowledge as strategy for poverty reduction in Tanzania. The specific objectives of this study were to understand the local community’s perception regarding the effects of entrepreneurial skills and knowledge, examined what are the key driving forces that make rural areas relevant to rural tourism, and to examine the destination-controlled challenges that militates its sustainability. The methods used included structured questionnaires, stakeholder’s key informant interviews, and reviews of relevant literature. A likert scale range from 1 to 7 was used to measure the level of ranking and acceptance of variables from the sample of 100 respondents. SPSS software version 20 was used in all methods to analyze multivariate analysis. Findings revealed that entrepreneurial skills and knowledge is the most important dimension to explain rural tourism performance as opportunities for poverty reduction in local communities. Thus, it was recommended that there was a need to institute entrepreneurial training and tourism programmes that would ultimately provide chance for rural communities to be employed in high cadres with high pay, all tourism stakeholders have to provide enabling environment conducive for the smooth operation of both indigenous entrepreneurs and foreign investors. Further, there should be sound national tourism economic policy with respect to Small Medium Enterprises (SMEs) to make sure that rural tourism is promoted effectively and the community to integrate its marketing and products strategies. Areas for further research are also suggested.